2016
DOI: 10.1136/thoraxjnl-2015-207604
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia upregulates neutrophil degranulation and potential for tissue injury

Abstract: BackgroundThe inflamed bronchial mucosal surface is a profoundly hypoxic environment. Neutrophilic airway inflammation and neutrophil-derived proteases have been linked to disease progression in conditions such as COPD and cystic fibrosis, but the effects of hypoxia on potentially harmful neutrophil functional responses such as degranulation are unknown.Methods and resultsFollowing exposure to hypoxia (0.8% oxygen, 3 kPa for 4 h), neutrophils stimulated with inflammatory agonists (granulocyte-macrophage colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 40 publications
10
92
0
2
Order By: Relevance
“…Consistent with these results, pharmacological and genetic HIF-1a knockdown decreased NET production and inhibited extracellular bacterial killing [74]. However, in vitro NET formation under true hypoxia has been shown to be diminished [71]. As NETosis is predominantly dependent on NADPH production of ROS [75], and therefore reliant on availability of molecular oxygen, it seems likely that NET production under hypoxia would be reduced in line with the ROS data, though it appears that HIF1a signalling also has a role to play.…”
Section: Neutrophil Extracellular Trapssupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with these results, pharmacological and genetic HIF-1a knockdown decreased NET production and inhibited extracellular bacterial killing [74]. However, in vitro NET formation under true hypoxia has been shown to be diminished [71]. As NETosis is predominantly dependent on NADPH production of ROS [75], and therefore reliant on availability of molecular oxygen, it seems likely that NET production under hypoxia would be reduced in line with the ROS data, though it appears that HIF1a signalling also has a role to play.…”
Section: Neutrophil Extracellular Trapssupporting
confidence: 72%
“…As such, hypoxia enhanced the release of multiple granule products, including MMP-9, lactoferrin and active NE and MPO from stimulated human neutrophils [71]. HIF-1a siRNA knockdown reduced protein levels of murine b-defensins and cathelicidin-related antimicrobial peptide (analogous to human antimicrobial peptide LL-37) in a mouse model of pseudomonal infection [61].…”
Section: Granule Exocytosismentioning
confidence: 99%
“…Potera et al noted involvement of p38 and ERK1/2 in TNF‐augmented granule release, but ROS suppressed the magnitude of this response, suggesting a negative feedback role. Consistent with this, our group has shown that hypoxia sufficient to suppress NADPH oxidase function enhances primed (GM‐CSF or PAF) neutrophil degranulation in a PI3Ky‐dependent fashion …”
Section: Signalling Priming Responses In Vivo and In Vitrosupporting
confidence: 71%
“…Consistent with this, our group has shown that hypoxia sufficient to suppress NADPH oxidase function enhances primed (GM-CSF or PAF) neutrophil degranulation in a PI3Ky-dependent fashion. 40 Primed granule exocytosis is tightly regulated and hierarchical; in an in vivo skin blister model, complete mobilisation of secretory vesicles was accompanied by discharge of 38% of tertiary, 22% of secondary and just 7% of primary granule proteins. 41 A similar rank order of degranulation was observed in response to calcium ionophore, and calcium chelation abolishes secretion of all but secretory vesicles.…”
Section: Priming Of Neutrophil Degranulationmentioning
confidence: 99%
“…Reports have linked IL‐8 to neutrophil survival and more controversially to NETosis induction . The hypoxic environment of a tumor or the gut may also contribute to NETosis as it increases neutrophil adhesion, degranulation, and toxicity . NETs may accelerate tumorigenesis as ROS, RNS, neutrophil elastase (NE), cathepsin G, and matrix metalloproteinases (MMPs) released by NETs may promote DNA mutations, mitogenesis, inhibit T‐cell activation, and spur on tumor invasion and metastasis .…”
Section: Tan Mechanisms In the Tumormentioning
confidence: 99%